Translation of measurement instruments and their reliability: an example of job-related affective well-being scale - Rode, Nino (Metodološki zvezki, 2005)
The translation of measurement instruments, like all cross-cultural research, presents many problems for researchers. Because of cultural and linguistic differences, the questions or items can have quite different meaning in the translated instruments, thus threatening the validity and reliability of measurement. These problems are (or should be) addressed by translation back-translation procedure. To illustrate the problems, the case of Job-related Affective Well-Being Scale is presented. The scale was translated from English to Slovene and applied directly in the research without backtranslation or other form of testing the translation. The Cronbach's alphais used to compare reliability of the results obtained with original (English) version reported by authors of the scale and with the translated (Slovene) version. In the item analysis some items have been singled out as problematic by item diagnostics. Especially the item excited , translated as vznemirjen , is discussed, since it is possible that backtranslation procedure could fail to detect the problem. At the end some tentative solutions are suggested.
Keywords: Measurement; Merjenje; Reliability; Zanesljivost; družboslovno raziskovanje; terminologija; terminology